Metrnl/Meteorin-like/IL-41, a novel regulator of bone metabolism and disease activity in ankylosing spondylitis: based on multi-omics analysis - Li, Zhuoqi; Sun, Tao; Zhao, Min; Xia, Liping; Shen, Hui (Frontiers in Immunology, 2025)
BackgroundAnkylosing spondylitis (AS) is an autoimmune disease characterized by bone destruction and abnormal remodeling. Metrnl, a secreted protein involved in inflammation and immune regulation, has recently been linked to bone growth. This study aimed to evaluate serum Metrnl levels in AS patients and explore its bone regulatory mechanisms using cell models and multi-omics analyses.MethodsA total of 275 participants aged 16–60 years were included to measure serum Metrnl levels using Enzyme-Linked-Immunosorbent Assay (ELISA). Correlation and receiver operating characteristic (ROC) curve analyses assessed the diagnostic and predictive value of Metrnl. Mouse pre-osteoblastic MC3T3-E1 cells were treated with recombinant Metrnl (0/10/50 ng/mL) during 28-day osteogenic differentiation. RT-qPCR and alkaline phosphatase (ALP)/Alizarin Red S (ARS) staining was used to evaluate direct osteogenic differentiation effects. Transcriptomic and proteomic studies were conducted to further explore bone metabolism mechanisms. Finally, multi-omics integration analyses identified key pathways and targets.ResultsElevated serum Metrnl levels correlated directly with disease activity markers (CRP, ESR, IL-6) in AS-Active patients, but not in AS-Stable patients. ROC analysis validated Metrnl as a potential auxiliary diagnostic biomarker for high disease activity. In vitro, Metrnl suppressed ALP/OCN expression without altering overall osteogenic differentiation. Transcriptomic and proteomic analyses revealed Metrnl’s regulatory effects on osteogenic genes and proteins, emphasizing its role in bone and cartilage development. Bioinformatics highlighted Metrnl’s inhibition of endochondral ossification, delaying cartilage development and promoting osteoclast differentiation. Multi-omics integration identified Aspn and Sp7 as key targets in bone remodeling and resorption balance.ConclusionsMetrnl may serve as an additional diagnostic biomarker for AS and as an indicator for monitoring AS disease activity. Besides, Metrnl plays a critical role in regulating cartilage and bone metabolism and maintaining bone homeostasis, providing new insights for the future diagnosis and treatment of bone-related diseases.